2010
DOI: 10.5551/jat.5371
|View full text |Cite
|
Sign up to set email alerts
|

Associations of 18-Year-Old Daughters' and Mothers' Serum Leptin, Body Mass Index and DXA-Derived Fat Mass

Abstract: Aim and Methods:We assessed the relationship of the body mass index (BMI) of 187 college female students aged 18 years with the reported BMI of their middle-aged biological parents measured on 2 occasions: when the parents were 18 − 20 years old and at the time of the study. The relationships of fat mass measured using whole body dual energy X-ray absorptiometry (DXA) and serum leptin levels were also determined between 148 daughters and middle-aged parents (148 mothers and 59 fathers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Previous studies also showed a greater influence of maternal BMI on childhood adiposity than paternal BMI [26][27][28] . Sun et al have reported that, based on data obtained in 2002, maternal obesity was more strongly associated with adolescent obesity than was paternal obesity in 2,842 males and 2,911 females aged 12 to 13 years in Japan 29) .…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies also showed a greater influence of maternal BMI on childhood adiposity than paternal BMI [26][27][28] . Sun et al have reported that, based on data obtained in 2002, maternal obesity was more strongly associated with adolescent obesity than was paternal obesity in 2,842 males and 2,911 females aged 12 to 13 years in Japan 29) .…”
Section: Discussionmentioning
confidence: 89%
“…We reported in another set of daughter-mother pairs that the mean BMI of mothers increased from 20.0 kg/m 2 at 18 years old to 21.8 kg/m 2 at 48 years old 33 . The BMI of 18-year-old daughters (20.2 kg/m 2 ) was associated not only with their mothers’ BMI when they were 18 years old but with the current BMI of their mothers.…”
Section: Discussionmentioning
confidence: 86%
“…We reported in another set of daughter-mother pairs that a mean BMI of mothers increased from 20.0 kg/m 2 at 18 years old to 21.8 kg/m 2 at 48 years old [33]. The BMI of 18-year-old daughters (20.2 kg/m 2 )…”
Section: Discussionmentioning
confidence: 89%